Sustainable exploration of coffee extracts (coffea arabica l.) for dyeing of microwave-treated bio-mordanted cotton fabric - ÖZOMAY, MERAL (My University, 2023)
Purpose This study aims to observe the coloring efficacy of coffee-based natural brown colorant for cotton dyeing under microwave (MW) treatment. Design/methodology/approach The colorant extracted in particular (neutral and acidic) media was stimulated by MW treatment up to 6 min. Dyeing variables were optimized and 2-10 g/100 mL of sustainable anchors (mordants) have been used to get colorfast shades. Findings It has been found that un-irradiated acidic extract (RE) containing 5% of table salt at 80 degrees C for 50 min has given high color yield onto MW-irradiated cotton fabric (RC = 2 min). The utilization of 2% of Fe, 10% of tannic acid and 10% of sodium potassium tartrate before bio-coloration, whereas 4% of Fe, 10% of tannic acid and 6% of sodium potassium tartrate after bio-coloration has given good color characteristics. In comparison the application of 6% of pomegranate and turmeric extracts before bio-coloration and 6% of pomegranate and 10% of turmeric extracts after bio-coloration have given good color characteristics. New bio-mordants can be added to get more new colorfast shades. Research limitations/implications There is no research limitation for this work. New bio-mordants can be added to get more new colorfast shades. Practical implications This work has practical application for artisans, textile industry and handicrafts. It is concluded that colorant from coffee beans can be possible alternative of synthetic brown dyes and inclusion of MW rays for extraction and plant molecules as shade developers can make process more green. Social implications Socially, it has good impact on eco-system and global community because the effluent load is not carcinogenic in nature. Originality/value The work is original and contains value-added product for textiles and other allied fields.
Keywords: Kimya Mühendisliği ve Teknolojisi; Kimya; Diğer; Temel Bilimler; Mühendislik ve Teknoloji; Chemical Engineering and Technology; Chemistry; Other; Natural Sciences; Engineering and Technology; KİMYA, UYGULAMALI; Temel Bilimler (SCI); MÜHENDİSLİK, KİMYASAL; Mühendislik; Mühendislik, Bilişim ve Teknoloji (ENG); MALZEME BİLİMİ, KAPLAMALAR VE FİLMLER; Malzeme Bilimi; CHEMISTRY, APPLIED; CHEMISTRY; Natural Sciences (SCI); ENGINEERING, CHEMICAL; ENGINEERING; Engineering, Computing & Technology (ENG); MATERIALS SCIENCE, COATINGS & FILMS; MATERIALS SCIENCE; Genel Malzeme Bilimi; Genel Mühendislik; Mühendislik (çeşitli); Kimya (çeşitli); Genel Kimya; Proses Kimyası ve Teknolojisi; Akışkan Akışı ve Transfer İşlemleri; Kolloid ve Yüzey Kimyası; Kimyasal Sağlık ve Güvenlik; Kataliz; Kimya Mühendisliği (çeşitli); Genel Kimya Mühendisliği; Fizik Bilimleri; General Materials Science; General Engineering; Engineering (miscellaneous); Chemistry (miscellaneous); General Chemistry; Process Chemistry and Technology; Fluid Flow and Transfer Processes; Colloid and Surface Chemistry; Chemical Health and Safety; Catalysis; Chemical Engineering (miscellaneous); General Chemical Engineering; Physical Sciences; Bio-mordanting; Coffee; Cotton; Microwave radiation; Sustainability; COLORANT